Determinan Keputusan Mahasiswa Dalam Berinvestasi - Dinatonia Jovery Matruty; Johanis Darwin Borolla; Erfendi Regar (Univiversitas Dr. Djar Wattiheluw, 2021)
Investment decisions are decisions made by managing assets or income owned to get profits in the future. This research wasconducted by observing 110 students who are currently studying at Pattimura University, Faculty of Economics and Business, majoring in Accounting and Management. The research analysis uses quantitative analysis by looking at the relationship between the Independent variables Investment Knowledge, Investment Motivation, Investment Interest, Information Technology, InvestorBehaviours, Investor Perception and Financial Literacy on Investment Decisions. The results of the study show that Investment Knowledge, Investment Interest, Information Technology, Investor Perception and Financial Literacy have a positive and significant influence on Investment Decisions. Meanwhile, Investment Motivation and Investor behaviours have no influence on Investment Decisions.